Conceptualizing ‘cannabis harm reduction’: lessons learned from cannabis compassion clubs and medical dispensaries in British Columbia (Canada) - Marilou Gagnon; Heather Hobbs (Harm Reduction Journal)
Abstract Objectives Drawing on a qualitative case study of cannabis compassion clubs and medical dispensaries in British Columbia (Canada), the main goal of this paper is to generate insights that have the potential to advance and broaden the conceptualization of ‘cannabis harm reduction’. Methods We undertook a qualitative case study by drawing on seven data sources: (1) online content, (2) news stories, (3) legal documents, (4) policy documents, (5) information about enforcement, (6) interviews with (i) key informants, (ii) participants with operational experience (i.e., people engaged in the active operations of compassion clubs/dispensaries in various roles), and (iii) participants with lived experience of medicating with cannabis, and finally (7) field notes. For this paper, we applied a harm reduction lens to the participant interview data. Results Applying a harm reduction lens to the participant interview data allowed us to identify two main conceptual dimensions: structural and operational. The structural dimension focused on the work undertaken by cannabis compassion clubs and medical dispensaries to address a risk environment created by systems, laws, and policies. The main themes identified here were access, safety, and quality. The operational dimension focused on the characteristics of the services provided cannabis compassion clubs and medical dispensaries. The main themes identified here were low-threshold, compassion, and supports. Our findings suggest that these two dimensions worked together to generate conditions conducive to ‘cannabis harm reduction’. Conclusions Based on our findings, we identified research, policy, and advocacy implications. We argue that research should focus on loss of access, regulation, a broader conceptualization of cannabis substitution, and better integration between cannabis and harm reduction. We also highlight the need for a harm reduction analysis of the Cannabis Act, new community-oriented models to meet the needs of people who medicate with cannabis, and non-profit supply pathways. Finally, we suggest that structurally-oriented advocacy is needed to achieve community-oriented models of cannabis cultivation, distribution, and consumption and that this advocacy would benefit harm reduction more broadly.